A confidence map based damage assessment approach using pulsed thermographic inspection - Zhao, Yifan; Addepalli, Sri; Sirikham, Adisorn; Roy, Rajkumar (Elsevier, 2017)
In the context of non-destructive testing, quantification of uncertainty caused by various factors such as inspection technique, testing environment and the operator is important and challenge. This paper introduces a concept of contour-based confidence map and an application framework for pulsed thermography that offers enhanced flexibility and reliability of inspection. This approach has been successfully applied to detect three flat-bottom holes of diameter 32, 16 and 8 mm drilled onto a 5 mm thick aluminium plate with a high accuracy of damage detection (R > 0.97). Its suitability and effectiveness in assessing impact damage occurring in composites have also been demonstrated.
Keywords: NDT; Reliability; Thermography; Impact damage assessment; Composite